Low-pressure calcination to enhance the calcium looping process for thermochemical energy storage. (20th August 2022) - Ortiz, C.; Carro, A.; Chacartegui, R.; Valverde, J.M.; Perejón, A.; Sánchez-Jiménez, P.E.; Pérez-Maqueda, L.A.
Abstract: The Calcium-Looping (CaL) process, based on the multicyclic calcination-carbonation of CaCO3 /CaO, is considered a promising Thermochemical Energy Storage (TCES) technology to be integrated into Concentrating Solar Power (CSP) plants. This work proposes a novel CaL integration that operates at low-pressure calcination under pure CO2 and a moderated temperature. Low-pressure calcination (0.01 bar) provides a suitable solution to mitigate CaO sintering and its consequent loss of reactivity in the carbonation stage. Since the temperature for quick calcination in a pure CO2 atmosphere is decreased (from around 950 °C at 1 bar to 765 °C at 0.01 bar), the energy losses at the receiver are minimised. In addition, a reduced calcination temperature allows for the use of metallic receivers already tested at the MW-scale, which significantly increases the CSP-CaL integration reliability. Moreover, multicycle CaO reactivity is promoted in short residence times, allowing the use of a simpler reactor design. Furthermore, there is an increase of 85% in the energy storage density of the system. The proposed plant proposes a smooth integration of the CaL process in CSP plants, with a moderate storage level and supported by a natural gas backup system (solar share higher than 50%). The results show that the solar thermal-to electric efficiency is above 30%.